Microstructural evolution in Fe-Cr-B based alloy powder and thermally sprayed coatings and their wear performance - Chokethawai, Komsanti (2010)
To date, the development of an amorphous alloy has concentrated entirely on a multi-component Fe-based amorphous alloy (Fe-Cr-B based alloy systems) containing boron and/or carbon. The major driving force behind these developments lies in the desire to produce an amorphous coating which exhibits both excellent thermal stability and wear performance, whilst achieving significant cost reductions over existing materials used in wear applications.